High in vitro antiurolithiatic effect of Pituranthos scoparius roots extracts - Yousfi, M; Benalia, H; Djeridane, A; Bensafieddine, F (PhOL, 2016)
The richness of the steppe zone by the medicinal plants and their diversity traditional uses in the region of Laghouat, allowed us to study the inhibitory effect of Herniaria fontanesii J.Gay, Pituranthos scoparius and Cynodon dactylon (L) extracts on the formation of calcium oxalate kidney stones. Firstly, we have carried out phytochemical screening and quantitative analysis of phenolic compounds of various extracts from the three plants. The obtained results proved that our extracts are rich in catechic tannins and C-, O-heterosides, with a total phenolic content ranged from 0.867 to 38.835 mg of gallic acid equivalent per 1 g of dry matter. The in vitro antiurolithiatic activity of different plants extracts has been carried out by two different models. In the turbidimetric assay, we have determined spectrophotometrically the effect of the extracts (1 g/L) on the oxalocalcic crystallization, induced by addition of oxalate in urines from healthy subject. Whereas, the gravimetric assay is based to measure the variation of calcium urate and uric acid renal calculi weight, after putting them in contact with 5 ml of the extracts (5g/L) during 15 days. In the two assays, the antiurolithiatic activity was compared with that of two antiurolithogenesis inhibitory standards: sodium citrate and Succinimide pharbiol. The achieved results measured by the two tests, show clearly that the hydromethanolic extracts of Pituranthos scoparius roots have provided very important antiurolithiasic power (>40% of inhibition) compared to the standard inhibitors. However, this result is a great step forward towards the search for an effective treatment for the urinary calculi formation. But, this work will have to be confirmed by in vivo experiments in order to validate these in vitro observations on the contributions of these three plants in the treatment of the oxalocalcic renal calculi.
Keywords: Medicinal plants; Pituranthos scoparius roots; phytochemical screening; kidney stones; Calcium oxalate; antiurolithiasic